Combined Acquisition and Tracking Methods for GPS L1 C/A and L1C Signals. (30th September 2010) - Macchi-Gernot, Florence; Petovello, Mark G.; Lachapelle, Gérard
Abstract : As part of the GPS modernization, the GPS L1 C/A signal will be augmented by the L1C signal. With this improvement, for the first time, several signals from the same constellation will be available at the same frequency. In this paper, an acquisition method is implemented to combine the GPS L1 C/A and L1C signals before correlation. The combined acquisition succeeds to acquire the signal at low C/N0, whereas the acquisition of the L1C data channel alone fails. Concerning the tracking, a method to combine the GPS L1 C/A and L1C signals before the discriminator is developed. This method shows better performance than the traditional tracking using only one signal. Finally, a Kalman filter to combine the signals in the tracking is developed. It shows better performance than the traditional tracking in all conditions. Since the L1C signal will not be broadcast before 2013, these methods are tested using a software signal simulator.